TQM, SCM and operational performance: an empirical study of Indian pharmaceutical industry. Issue 1 (1st August 2019) - Sharma, Sanjay; Modgil, Sachin
Abstract : Purpose: The purpose of this paper is to investigate the impact of total quality management (TQM) and supply chain management (SCM) practices on operational performance, and their interlinkage between each other. Design/methodology/approach: Constructs those are critical to pharmaceutical quality and supply chain have been identified with the help of literature and experts from industry. The impact of TQM practices on supply chain practices and on operational performance has been evaluated. Similarly, the impact of supply chain practices on operational performance has been evaluated. Further, alternate models are tested and evaluated through structural equation modeling. Findings: It was observed during testing of alternate models that TQM practices have a direct impact on operational performance. However, TQM practices also directly impact supply chain components, which, in turn, influence overall operational performance. In comparison of alternate models, the model in which TQM practices affect supply chain practices and supply chain practices further affect the operational performance is found most appropriate. Practical implications: This study provides some useful implications from industry point of view. TQM practices are critical to pharmaceutical industry. TQM practices are the core of attaining a smooth supply chain, which will have greater impact to achieve operational performance. Strategic supplier partnership, procurement management, information sharing, and quality and inventory management practices are driven by TQM practices. This tri-linkage helps to achieve the desired operational performance. Originality/value: There are very limited studies that have considered both the areas together to achieve better operational performance. In pharmaceutical industry, both TQM and SCM are the critical areas for any organization to drive its growth.